Media Convergence: the Realization of Monopoly and Oligopoly in Indonesia" - Nanda, Muhammad Afriyan Putra; Ardilla, Yunda Presti (Semantik: Journal of Social, Media, Communication, and Journalism, 2023)
This study aims to explore the evolution of media convergence in Indonesia, focusing on Kompas Gramedia as a leading media entity that has undergone rapid development. Its business expansion has surged, particularly in the realm of digital media, significantly broadening its market share in Indonesia. Employing a qualitative descriptive approach and utilizing a case study method centered on Kompas Gramedia and its subsidiaries, this research gathers data from credible sources. Through comparative and correlational analyses, it highlights the changing landscape of media convergence within Kompas Gramedia. Initially established as a print-based medium, Kompas Gramedia has undergone a transformation towards digital media and digital television. This transformation signifies the prevalence of monopolistic and oligopolistic practices in the Indonesian media industry, thriving through media convergence strategies. The findings underscore the dynamic shift from traditional print to digital platforms, showcasing how media entities adapt and monopolize within an evolving technological landscape.┬áThis study sheds light on the intricate relationship between media evolution, market dominance, and the strategic maneuvers employed by major media players like Kompas Gramedia in Indonesia's ever-expanding digital ecosystem.